2022
DOI: 10.1159/000525574
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatinine Patterns in Neonates Treated with Therapeutic Hypothermia for Neonatal Encephalopathy

Abstract: <b><i>Introduction:</i></b> There is large variability in kidney function and injury in neonates with neonatal encephalopathy (NE) treated with therapeutic hypothermia (TH). Acute kidney injury (AKI) definitions that apply categorical approaches may lose valuable information about kidney function in individual patients. Centile serum creatinine (SCr) over postnatal age (PNA) may provide more valuable information in TH neonates. <b><i>Methods:</i></b> Data from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Using the published TH ( caling SCr biomarker approach," described by Pottel et al [5]. In essence, we calculated the SCr TH /Scr controls ratio (TH to controls) for 10th-25th-50th-75th-90th centiles as published in the Neonatology paper and its supplement [2]. In the event of "similar SCr values,ˮ the centiles for this ratio should be straight lines around 1.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Using the published TH ( caling SCr biomarker approach," described by Pottel et al [5]. In essence, we calculated the SCr TH /Scr controls ratio (TH to controls) for 10th-25th-50th-75th-90th centiles as published in the Neonatology paper and its supplement [2]. In the event of "similar SCr values,ˮ the centiles for this ratio should be straight lines around 1.…”
Section: Dear Editormentioning
confidence: 99%
“…Fig.1. Based on the centiles (10th, 25th, 50th, 75th, and 90th) SCr values over PNA (day 1-day 7) previously reported in the TH (1,136 cases, 4,724 SCr values) and the control (801 cases, 2,779 SCr values) group, the SCr TH / SCr controls ratio has been calculated[2,5]. Black continuous lines: P10, P50, and P90; grey discontinuous lines: P25 and P75; black discontinuous line: line of "equal" ratio.…”
mentioning
confidence: 99%
“…This resulted in better identification of risk groups (“precision medicine”), development of prediction models (like urinary neutrophil gelatinase-associated lipocalin (NGAL) after cardiac surgery) ( 7 ). Alternatively, a suggestion to consider a centile approach (somewhat similar to commonly used growth charts) over postnatal age has been applied to extreme low birth weight (ELBW) infants, and more recently, to neonates treated with therapeutic hypothermia for neonatal encephalopathy ( 6 , 8 ).…”
mentioning
confidence: 99%
“…When we look at their data (Table 2; Fig. 1a–d) [1], we see a downward trend in SCr level among all cases. For example, neonates with acute kidney injury (AKI) and with no AKI had a downward trending pattern irrespective of the initial value.…”
mentioning
confidence: 99%
“…Dear Editor, I read with interest the article by Keles et al [1], describing serum creatinine (SCr) centiles in neonates treated with therapeutic hypothermia (TH). They suggested that a centile-based approach could guide pharmacotherapy, fluid management, and kidney-supportive therapies.…”
mentioning
confidence: 99%